Cloning of Baeyer‐Villiger monooxygenases from Comamonas , Xanthobacter and Rhodococcus using polymerase chain reaction with highly degenerate primers - Jan B. Van Beilen; Frédéric Mourlane; Markus A. Seeger; Jasminka Kovac; Zhi Li; Theo H. M. Smits; Urban Fritsche; Bernard Witholt (Environmental Microbiology, 2003)
Summary To clone novel type 1 Baeyer‐Villiger monooxygenase (BVMO) genes, we isolated or collected 25 bacterial strains able to grow on alicyclic compounds. Twelve of the bacterial strains yielded polymerase chain reaction (PCR) fragments with highly degenerate primers based on the sequences of known and putative BVMOs. All these fragments were found to encode peptides homologous to published BVMO sequences. The complete BVMO genes and flanking DNA were cloned from a Comamonas , a Xanthobacter and a Rhodococcus strain using the PCR fragments as probes. BVMO genes cloned from the first two strains could be expressed to high levels in Escherichia coli using standard expression vectors, and the recombinants converted cyclopentanone and cyclohexanone to the corresponding lactones. The Rhodococcus BVMO, a putative steroid monooxygenase, could be expressed after modification of the N‐terminal sequence. However, recombinants expressing this protein did not show activity towards progesterone. An esterase homologue located directly upstream of the Xanthobacter BVMO gene and a dehydrogenase homologue encoded directly downstream of the Comamonas sp. NCIMB 9872 BVMO gene were also expressed in E. coli and shown to specify lactone hydrolase and cyclohexanol dehydrogenase activity respectively.